SYLLABLE DIVISION IN ENGLISH (The Role of Exact Sciences in the Era of Modern Development, 2024)
presented article indicates the syllabic structure of English language and the rules of phonetic syllable division. Also there has been stated about factors that determine the rules for syllable vision, free and checked character of the vowels, monophthongs and dipthongs, a syllable boundary English affricates. Moreover, characteristics of syllabic consonentsalso have been stated Sometimes a syllable consists phonetically only of a consonant or consonants. Such a consonant is a syllabic consonant.